2010
DOI: 10.1016/j.ejvs.2010.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vein Thrombosis (DVT) after Venous Thermoablation Techniques: Rates of Endovenous Heat-induced Thrombosis (EHIT) and Classical DVT after Radiofrequency and Endovenous Laser Ablation in a Single Centre

Abstract: The DVT rate including EHIT was similar in patients treated with RFA and EVLA and was low. Routine post-operative duplex ultrasound scanning is recommended until the significance of EHIT is better understood, in accordance with consensus guidelines. DVT rates for both techniques compare favourably with those published for saphenous vein stripping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
117
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(130 citation statements)
references
References 25 publications
5
117
0
6
Order By: Relevance
“…Van Rij et al (16) documented DVT in 5.3% of their patients' limbs after varicose vein surgery; however, the majority of these thrombi were localized to the tibial veins. As demonstrated by previous trials and case studies, DVT in patients who have undergone EVLA is rare, with a reported incidence of 0% to 6% (6,17).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Van Rij et al (16) documented DVT in 5.3% of their patients' limbs after varicose vein surgery; however, the majority of these thrombi were localized to the tibial veins. As demonstrated by previous trials and case studies, DVT in patients who have undergone EVLA is rare, with a reported incidence of 0% to 6% (6,17).…”
Section: Discussionmentioning
confidence: 96%
“…EHIT is thrombus extension into a deep vein after a superficial venous thermoablation that usually carries a benign prognosis (17). Marsh et al (17) observed an incidence of DVT of 1% after EVLA.…”
Section: Discussionmentioning
confidence: 99%
“…8,20 With regard to DVT rates, our findings are also similar to other studies of laser treatment and rates are similar, if not lower than, those for patients treated using conventional surgery. 23,24 With regard to less serious intercurrent conditions, we believe that longer wavelengths may benefit patients in terms of reduced postoperative pain and lower degree of ecchymosis when compared with patients treated with shorter wavelengths. 4,17 The explanation for this is the fact that shorter wavelengths have a greater affinity for deoxygenated hemoglobin and so heat up the intraluminal blood, leading to significant transmission of heat to adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…5,6) Duplex ultrasonography is considered mandatory after catheter ablation therapy to screen for occlusion of ablated vessels and complications such as deep venous thrombosis, with the incidence of EHIT reportedly ranging from 0% to 15.5%. 7,10) …”
Section: Discussionmentioning
confidence: 99%